A provably secure identity‐based proxy ring signature based on RSA. Issue 7 (21st July 2014) - Asaar, Maryam Rajabzadeh; Salmasizadeh, Mahmoud; Susilo, Willy
Abstract: Proxy ring (anonymous proxy) signatures allow an entity to delegate its signing capability to a group of entities (proxy group) such that only one of the members in the proxy group can generate a proxy signature on behalf of the delegator, while privacy of the proxy signer is protected. Identity‐based versions of proxy ring signatures employ identity strings in place of randomly generated public keys. Our contribution is twofold. First, we formalize a security model for identity‐based proxy ring signatures. We note that there exists no formal security model for identity‐based proxy ring signatures prior to our work. Second, we present the first provably secure identity‐based proxy ring signature scheme using a new paradigm called sequential aggregation. The construction is proved secure, under the one‐wayness assumption of RSA, in the random oracle model by presenting a new forking lemma. We should highlight that the proxy key exposure attack cannot be applied to our scheme. Further, in contrast to the existing schemes that are based on pairings, our scheme is based on RSA; therefore, it outperforms the existing schemes in terms of efficiency and practicality. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : In this paper, we formalize a security model for identity‐based proxy ring signatures for the first time. Then, we present the first provably secure scheme for this primitive using a new paradigm called sequential aggregation under the RSA assumption, in the random oracle model. The proxy key exposure attack cannot be applied to our scheme, and also it outperforms the existing schemes in terms of efficiency and practicality.